The Impact of English Movies with Standard Subtitles on Enhancing the Writing Skills of EFL Students at Cihan University – Duhok - Omar, Khadija Saleem; Mohammed Salman, Nahida; Vadivel, Balachandran (International Journal of Humanities and Education Development (IJHED), 2023)
This research paper aims to comprehensively investigate the effects of English movies accompanied by standard English subtitles on the writing skills of English as a second language (ESL) learners. Writing, considered a particularly challenging language skill, presents unique difficulties for ESL learners. Moreover, understanding English movies without subtitles poses further challenges. To address these issues, integrating media and movies into language learning practices has been recognized as highly effective. This study employs a meticulously designed questionnaire as the primary research instrument to collect data from a sample size of 30 participants aged 19-24 enrolled at Cihan University- Duhok. A combination of qualitative and quantitative methodologies is utilized to thoroughly examine the impact of watching English movies with English subtitles on the development of writing skills. Participants provide valuable insights into the effects they experience when utilizing subtitles, including improvements in expressive abilities, as well as the formation of more coherent and sophisticated sentences and phrases. The findings unequivocally demonstrate that a significant majority of participants attribute their enhanced writing skills to the use of English movies with subtitles as a powerful learning tool.